Urethanes and polyurethanes from suberin: 1. Kinetic study - Cordeiro, Nereida (2021)
Within the context of a study on the preparation and the characterization of polyurethanes based on suberin, as a polyol, and conventional polyisocyanates, it was deemed necessary to carry out a preliminary study on the reactivity of the hydroxy functions of suberin. Aliphatic and aromatic mono- and di-isocyanates were tested and the kinetics of this system followed the classical second order up to conversions of about 85%. The influence of the steric hindrance and the electronic factors, linked to the specific structures of both types of isocyanates, was established.